Enabling the thermal stability of solid electrolyte interphase in Li‐ion battery. Issue 6 (4th May 2021) - Zu, Chenxi; Yu, Huigen; Li, Hong
Abstract: Lithium‐ion batteries (LIBs) provide power for a variety of applications from the portable electronics to electric vehicles, and now they are supporting the smart grid. Safety of LIBs is of paramount importance in these scenarios. Specifically, thermal safety arouses increasing attention with the piling‐up of LIBs. Heat generation can be significant. Hazardous incidents happen when thermal runaway occurs in a single cell level and drives the battery pack failure. Moreover, thermal runaway of LIBs is believed to originate from the exothermic reactions starting from the breakdown of the solid/cathode electrolyte interphase (SEI/CEI). To mitigate this challenge for a safe operation of LIBs, one straightforward and low‐cost method is to build thermally stable SEI/CEI. This review gives an overview on the thermal behaviors of SEI/CEI as the first step in thermal runaway. We analyzed the electrolyte composition and the formation process of SEI/CEI that enable SEI/CEI of high thermal stability. It is identified that the stable lithium salts coupled with solvents of high boiling point is one way to enhance thermal stability of the battery system. In addition, the unsaturated bonds, halogen, phosphorus, sulfur, phenol, organic borate, borane, and silane are functional components to facilitate the formation of a thermally stable SEI/CEI, which is the immediate solution to boost thermal stability of high capacity electrodes. Moreover, in‐situ polymerization/solidification is effective in enhancing simultaneously the electrochemical, chemical, and thermal stability. Finally, we revealed that only by constructing a stable SEI/CEI simultaneously could we harvest a battery system of high thermal stability. Abstract : Thermal stability of the solid/cathode electrolyte interphases (SEI/CEI) determines the onset temperature of thermal runaway of batteries, and should be screened and designed for rational purposes. In this review, failure mechanism of SEI/CEI is discussed and remedies are given for an enabling SEI/CEI thermally stable and batteries of high safety.